Customer Satisfaction Mediates Digital Banking Quality and Features on Reuse Intention: HSBC Indonesia Case - Jodiyosa, Puti; Winadi Prasetyoning Tyas, Ari Anggarani (APLIKATIF: Journal of Research Trends in Social Sciences and Humanities, 2025)
This study aims to examine the role of E-Service Quality and Internet Banking Features in influencing reuse decisions, with customer satisfaction acting as a mediating variable. The research focuses on Internet Banking users of HSBC Indonesia, Tomang Branch. A quantitative approach was employed using Structural Equation Modeling (SEM) with Partial Least Squares (PLS). A total of 200 respondents were selected using non-probability sampling and responded to a Likert-scale-based questionnaire. The results indicate that both E-Service Quality and Internet Banking Features do not have a direct significant effect on reuse decisions. However, they significantly influence customer satisfaction, which in turn has a strong direct impact on reuse decisions. Furthermore, customer satisfaction effectively mediates the relationship between E-Service Quality and Internet Banking Features on reuse intention. The findings suggest that enhancing privacy protection, ease of access, and interface design can improve customer satisfaction and drive customer loyalty in digital banking. The study is limited by its single institution focus and geographic scope, which may affect the generalizability of the findings. Future research is encouraged to include multiple banks and broader regional contexts to validate these results.